Traumatic childhood experiences and personality functioning: effect of body connection in a cross-sectional German and Chilean sample - Bertsch, Katja; Göhre, Isabelle; Cottin, Marianne; Zettl, Max; Wienrich, Carolin; Back, Sarah N. (Borderline Personality Disorder and Emotion Dysregulation, 2024)
Background: Traumatic childhood experiences are a major risk factor for developing mental disorders later in life. Over the past decade, researchers have begun to investigate the role of early trauma in impairments in personality functioning following the introduction of the Alternative Model of Personality Disorders in Section III of the Diagnostic and Statistical Manual for Mental Disorders 5. Although first studies were able to empirically demonstrate a significant link between early trauma and impairments in personality functioning, only little is known about the underlying mechanisms. One possible mechanism is body connection due to its involvement in self-regulatory processes and its link to both early trauma and personality (dys)functioning. Objective: In the current study, we investigated whether body connection, which encompasses the awareness, integration, and utilization of one’s own bodily signals, mediates the relationship between childhood trauma and personality functioning. Participants and setting: A total of 1,313 adult participants recruited in Germany and Chile anonymously provided self-report data in an online survey. Methods: Self-report data included the short form of the Childhood Trauma Questionnaire (CTQ-SF), the Scale of Body Connection (SBC), and the brief form of the Levels of Personality Functioning Scale (LPFS-BF 2.0) as well as demographic data (age, sex, education, clinical diagnoses). Results: Traumatic childhood experiences explained 27.2% of the variance in impairments in personality functioning. Interestingly, 60.5% of this effect was explained by body connection, particularly body dissociation. Additional exploratory analyses revealed that body dissociation and, to a much lesser extent, body awareness, accounted for 64.41% of the variance in self functioning and 55.75% of the variance in interpersonal functioning explained by childhood trauma. Conclusion: Body connection appears to be an important mediator in the association between early trauma and impaired personality functioning, underscoring the need for interventions specifically targeting the avoidance and ignorance of signals from one’s own body in individuals with traumatic childhood trauma.
Gesehen am 05.09.2025